Stolniceni, Petreni, Brînzeni, Republik Moldau. Luftbildaufnahmen mit Drohnen (UAV) von kupferzeitlichen Siedlungen in Moldawien im Kontext magnetischer Prospektionen und Ausgrabungen. Die Arbeiten der Jahre 2009 bis 2017 - Scholz, Roman; Rassmann, Knut; Terna, Stanislav (e-Forschungsberichte des DAI, 2018)
There are numerous Eneolithic settlements of the Cucuteni-Trypillia culture in North and Central Moldova. Its distribution ranges from the East of Romania via Moldova up to the Dnieper River. In Romania and Moldova settlements measure 10 to 30 ha, in Ukraine many are bigger than 100 ha. Indeed, these represent the largest settlements of Stone Age and Eneolothic Europe! During the 1970s and 1980s, Soviet Archaeologists started research on these by means of aerial photographs and magnetic prospections which has been continued by the Romano-Germanic Commission with their Moldovan and Ukrainian partners for a research project that started in 2009. Ahead of excavations, large-scale prospections have been conducted, first in Moldova and from 2011 onwards also in Ukraine. In 2017, the first aerial photographs of three of the most important sites in Moldova have been produced using drones. These pictures are being used foremost in order to create topographical maps and height models. Via the GIS based analysis of data it is possible to draw a more comprehensive picture of the phenomenon.